1988
DOI: 10.1093/jn/118.4.456
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Cysteine Dioxygenase Activity and Sulfur Amino Acid Metabolism in Rats: Possible Indicators in the Evaluation of Protein Quality

Abstract: Experiments were carried out to examine the possibility that the sulfur amino acid metabolism of rats may be an indicator of the nutritional value of dietary protein. Rats were fed diets containing 8, 16 or 24% of gluten, soy protein or casein for 3 wk. Hepatic cysteine dioxygenase activity, hepatic concentration of glutathione, cysteine and taurine and urinary taurine were examined. In addition, the sulfur amino acid metabolism of rats fed these diets fortified with the appropriate first limiting amino acid f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…Thus, our results extend the observations in mice to the situation in which the diet is only partially deficient in an essential amino acid (i.e. SAA), to an amino acid pattern that is more representative of that in diets consumed by humans and animals, and to a diet that has been shown to support both growth and longevity (29)(30)(31).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Thus, our results extend the observations in mice to the situation in which the diet is only partially deficient in an essential amino acid (i.e. SAA), to an amino acid pattern that is more representative of that in diets consumed by humans and animals, and to a diet that has been shown to support both growth and longevity (29)(30)(31).…”
Section: Discussionsupporting
confidence: 78%
“…A number of studies have shown an association of eIF2a phosphorylation with induction of a state of stress resistance in cells (29,30). This study now shows that modest SAA restriction can induce the ISR in liver of intact growing rats.…”
Section: Discussionmentioning
confidence: 99%
“…Diets were prepared by Dyets Inc. (Bethlehem, PA, USA). Sulfur amino acid levels were based on previous rat studies that demonstrated that 2.3 g methionine is adequate to meet the absolute requirement of growing rats for methionine (i.e., the requirement for methionine when cyst(e)ine is not limited in the diet) [29, 30]. For diet preparation, the powdered diets were mixed with an equal volume (1 L/kg diet) of hot agar solution (3 g/L), and the mixture was cooled at room temperature, refrigerated, and cut into cubes for feeding.…”
Section: Methodsmentioning
confidence: 99%
“…It is accepted that L-cysteinesulfinate is a key intermediate product both in the catabolic pathway to form pyruvate and sulfate, and in taurine biosynthesis pathway from L-cysteine in mammals as shown in Figure 1 (Yamaguchi and Hosokawa 1987a;Yamaguchi 1990). Therefore, cysteine dioxygenase (CDO) [EC 1.13.11.20] which catalyzes the oxygenation of L-cysteine to form Lcysteine sulfinate has been considered to participate in the regulation of sulfur amino acid metabolism in mammals (Daniels and Stipanuk 1982;Hosokawa et al 1988). Recently, we have observed that the CDO is present in the liver of rainbow trout, and that this enzyme was induced both by dietary supplementation of an excess amount of methionine and cystine, and by high protein diet as well (Yokoyama and Nakazoe 1989;Yokoyama et al 1994).…”
Section: Introductionmentioning
confidence: 99%